Divided World, Divided Religion: Western Roots, Muslim Problem - Cheng, Yamin (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The idea that religion is one segment of a total dimension of human existence, or that it is a product of the human mind and the human condition, is an idea of recent times. This idea could be traced to the Enlightenment and the Social Sciences, two Western intellectual movements of the eighteenth centuries respectively. Contemporary Muslim intellectuals attributed to Western imperialism and colonialism for the introduction of an idea of religion nurtured in Enlightenment thought and the Social Sciences into the Muslim understanding of religion. If we are to gauge to what extent this Muslim attribution is true it is the instrumental for us to understand the fate of religion in Western History.